Looking into urban toponymic verticality: An initial note - Sergei Basik (Urban Governance)
The current vertical/volumetric turn affected various academic fields, including urban scholarship. This short note broadens the critical literature by applying this emerging perspective on urban toponymic systems in the context of urban governance. Synthesizing the critical toponymic approaches with the notions of volume and verticality of urban space, this paper advanced critical urban governance scholarship, introducing a concept of toponymic verticality. The short note reveals the spatial vertical stratification of the urban toponymic system, its place-making potential, and political-economic functionality. These initial findings can contribute to future research in practical aspects of the politics of “good” urban governance and potentially rethinking the traditional two-dimensional spatiality toward understanding the complexity of the spatial relations in urban landscapes through the verticality of urban place names.